Dillenia Indica Fruit Extract Suppressed Diet-induced Obesity in Rats by Down-regulating the mRNA Level of Proadipogenic Transcription Factors and Lipid Metabolizing Enzymes - Kuddus, Syed A.; Tasnim, Zarin; Shohag, Md. H.; Yasmin, Tahmina; Uddin, Md. Sahab; Hossain, Muhammad M.; Subhan, Nusrat; Alam, Md. Ashraful; Khan, Ferdous (Current Nutrition & Food Science, 2021)
Background: Dillenia indica (Family: Dilleniaceae) is an antioxidant-rich edible fruitbearing medicinal plant. The fruit of this plant (known as elephant apple) has many uses in traditional medicine. Objective: By considering its antioxidant content and ameliorating effects, this study aimed to evaluate the anti-adipogenic effects of D. indica fruit extract (DIFE) on high-fat diet (HFD) fed obese rats. Methods: Male Wistar rats were fed with a standard diet (SD), or high-fat diet (HFD), or HFD with 100 mg/kg or 200 mg/kg or 400 mg/kg DIFE for 8 weeks. The fruit extract was given orally by feeding gavage. The body weight, liver weight, visceral fat weight, plasma lipids, and oxidative stress-related parameters were measured. The mRNA level of different adipogenesis related transcription factors, lipogenic and lipolytic enzymes was also evaluated. Results: Consumption of DIFE daily (400 mg/kg) for 8 weeks resulted in a significant reduction of high-fat diet-induced body weight, liver weight, visceral fat weight, total cholesterol, and LDL-cholesterol level. High-fat diet-mediated elevation of oxidative stress markers was also lowered, with a parallel augmentation of the activities of antioxidant enzymes, due to 400 mg/kg DIFE feeding. DIFE also down-regulated the mRNA level of important pro-adipogenic factors like PPARγ, LXRα, and SREBP1c which consequently downregulated the transcript levels of lipogenic enzymes: ACC, FAS, HMGCR, and DGAT. The transcript level of lipolytic enzyme, HSL was also down-regulated in 400 mg/kg DIFE-fed rats. Conclusion: These findings indicate that the antioxidant-rich ethanolic extract of D. indica fruit can down-regulate the gene expression of pro-adipogenic transcription factors and lipid metabolizing enzymes and thus can suppress diet-induced obesity in Wistar rat.
Keywords: oxidative stress